Labour force participation in the euro area: a cohort based analysis - Almut Balleer; Ramón Gómez-Salvador; Jarkko Turunen (European Central Bank (ECB), 2009)
We use a cohort based model to analyse determinants of labour force participation for disaggregated groups of workers in the euro area and the five largest euro area countries. The model captures age and cohort effects as indicators of (unobserved) determinants of participation behaviour. We use these effects and observed determinants to construct trends and projections of labour supply. Our results suggest that age and cohort effects can account for a substantial part of the recent increase in participation. Cohort effects are particularly relevant for women with those born in the late 1960s and early 1970s more likely to participate over the life-cycle. There is substantial variation in the estimated age and cohort effects across countries. Looking forward, positive cohort effects for women are not large enough to compensate for the downward impact of population ageing on participation rates in the euro area.
Keywords: J11; J21; 330; cohort analysis; labour force participation; Labour market institutions; Erwerbstätigkeit; Arbeitsangebot; Bevölkerungsentwicklung; Kohortenanalyse; Eurozone